MASCULİNİTY, OTHERNESS, AND HİERARCHY: THE CONSTRUCTİON OF MALE IDENTİTİES İN POST-1980 TURKİSH CİNEMA - Yelda Özkoçak, (PEOPLE: International Journal of Social Sciences, 2026)
This paper aims to examine representations of masculinity in post-1980 Turkish cinema and the ways these representations construct relationships with the “other.” The analysis is framed by Connell’s concept of hegemonic masculinity, Connell and Messerschmidt’s gender performance theory, and Laura Mulvey’s “male gaze” approach. This theoretical foundation helps explain how male characters are constructed around power, authority, and dominance, and how alternative forms of masculinity—the “othered men”—are marginalized. The study focuses on post-Yeşilçam social-realist films as well as independent Turkish cinema from the 1990s and 2000s. It analyzes how male characters attempt to reassert their authority in the face of social crises and how they interact and clash with female characters and other men. Cinematic techniques, such as camera angles, narrative structures, and spatial usage, are also examined to explore how male identities are performed on screen. Ultimately, this paper seeks to make visible the pluralistic representations of masculinity and the hierarchies constructed through otherness in post-1980 Turkish cinema. It discusses how gender norms are reproduced or challenged through film, thereby directly contributing to the theme of “Identity and Otherness in Film.” The approach combines theoretical insight with close film analysis, offering a robust framework for understanding the intersection of gender, identity, and cinematic representation in contemporary Turkish cinema.